Logistics resources on sustainable competitive advantage in Kurdistan Iraq: Hotels sector and LSPs perspective - Ahmad M.A.-A.; Jais J.; Khudari M. (American Institute of Physics Inc., 2023)
The ability to generate and maintain competitive advantage in supply chain is critical to an organization's survival, particularly in the era of globalization. However, there are a limited number of logistics service providers (LSPs) studies exploring sustainable competitive advantage in post-war countries. In post-war countries such as Iraq, organizations face various challenges to recover and achieve competitive advantage in the supply chain. Thus, the key objectives of this study are to examine the relationships between hotel's logistics resources and sustainable competitive advantage (SCA) in the context of tourism industry development in Kurdistan Region, Iraq. Questionnaire was used as data collection technique to measure the effect of logistics resources on SCA. The results showed that that there is strongly relationship between logistics resources and SCA in hotel industry. Therefore, the tourism in Kurdistan region needs continued government attention and supports. It is also critically vital to identify logistics resources to facilitate SCA, which may assist the new model's development in improving tourism industry in Kurdistan region of Iraq. 2022 Author(s).